Quality of life index in autoimmune bullous dermatosis patients - Penha, Mariana Alvares [UNESP]; Farat, Joyce Godoy [UNESP]; Miot, Helio Amante [UNESP]; Barraviera, Silvia Regina Catharino Sartori [UNESP] (Soc Brasileira Dermatologia, 2015)
Background: Autoimmune bullous dermatoses are complex diseases triggered by autoantibodies action against epidermal antigens or the dermoepidermal junction. Blisters and vesicles that evolve with erosion areas characterize them. Although rare, they present high morbidity, affecting the quality of life of patients.Objectives: To assess the magnitude of autoimmune bullous dermatoses on life quality of patients treated in a public university service in countryside of Brazil. Methods: This cross-sectional study was based on an inquiry with autoimmune bullous dermatoses patients assisted at outpatient university referral service. Elements related to quality of life were evaluated by the Dermatology Life Quality Index, as well as clinical and demographic data. Results: The study evaluated 43 patients with pemphigus foliaceus, 32 with pemphigus vulgaris, 6 with bullous pemphigoid and 3 with dermatitis herpetiformis. The average age was 48 +/- 16 years and 34 (40%) were female. The median score (p25-p75) of the Dermatology Life Quality Index was 16 (9-19), classified as "severe impairment" of life quality, in which the greater impact was related to symptoms and feelings, daily and leisure activities. Conclusions: Autoimmune bullous dermatoses inflict severe impairment of quality of life for patients followed by a public outpatient clinic in the countryside of Brazil.
Keywords: Dermatitis herpetiformis; Pemphigoid; Bullous; Pemphigus; Quality of life; Skin diseases; Vesiculobullous